Biomarkers for the identification of recurrence in human epidermal growth factor receptor 2-positive breast cancer patients. Issue 6 (November 2016) - Pruneri, Giancarlo; Bonizzi, Giuseppina; Vingiani, Andrea
Abstract : Purpose of review: This review discusses the mechanisms of anti-human epidermal growth factor receptor 2 (HER2) resistance in breast cancer patients, detailing possible predictive biomarkers of therapy benefit that could implement novel therapeutic strategies. Recent findings: Despite a remarkable improvement in survival over the past two decades, up to 30% of early-stage HER2+ breast cancer patients exhibit de-novo or acquired resistance to targeted therapy, underlying the need of developing predictive biomarkers. Summary: The role of HER family receptor redundancy, p95HER2 expression, and phosphoinositide 3-kinase/protein kinase B/mammalian target of rapamycin downstream pathway activation in counteracting the inhibitory effects of anti-HER2 targeted therapy has been addressed. We also discuss the possible inconsistencies in the definition of HER2 positivity according to American Society of Clinical Oncology/College of American Pathologists guidelines or molecular intrinsic subtypes, and address the role played by tumor heterogeneity and evolutionary clonal selection on therapy selective pressure. Finally, the interplay between adaptive immunity and anti-HER2 targeted therapy is extensively discussed, focusing on its putative predictive and prognostic role.